Climate Change on Environmental Health and the Spread of Infectious Diseases - Chang, Yuan; Li, Xinyan (TOPAZART, 2024)
The article examines the intricate relationship between climate change, environmental health, and the proliferation of infectious diseases. As global temperatures rise, shifts in weather patterns, and alterations in ecosystems are becoming increasingly evident. These environmental changes are facilitating the spread of infectious diseases by expanding the range of vectors, such as mosquitoes and ticks, and altering the timing and intensity of outbreaks. The article delves into the mechanisms through which climate change exacerbates the vulnerability of human populations to diseases like malaria, dengue fever, and Lyme disease. It also discusses the implications of these changes for public health infrastructure, particularly in regions already burdened by inadequate healthcare resources. The study emphasizes the need for interdisciplinary approaches that integrate climate science, epidemiology, and public health strategies to mitigate the impact of climate change on global health.